Implementation of post-fire debris-flow hazard assessments along drainage networks, southern california, U.S.A. - Gartner, Joseph E.; Cannon, Susan H.; Santi, Paul M. (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value="{"1":2,"2":"Burned watersheds in Southern California steeplands can be particularly susceptible to debris flow. Rapid assessments of potential debris-flow hazards following a fire are necessary to provide timely information to the public, land managers, and emergency-response agencies about locations most prone to debris- flow impact. Here we present a method to implement a set of existing debris-flow susceptibility models along a drainage network using input variables that are quantified for the contributing drainage basin areas to each grid cell along a drainage network. This method accounts for the spatially variable properties within contributing drainage basin areas as debris flows travel through the drainage network. Applying the models along drainage networks, rather than to an entire drainage basin, provides hazard assessments that identify the potential impacts within the primary channels of a watershed, where destructive debris flows may both erode and deposit large volumes of material."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Burned watersheds in Southern California steeplands can be particularly susceptible to debris flow. Rapid assessments of potential debris-flow hazards following a fire are necessary to provide timely information to the public, land managers, and emergency-response agencies about locations most prone to debris- flow impact. Here we present a method to implement a set of existing debris-flow susceptibility models along a drainage network using input variables that are quantified for the contributing drainage basin areas to each grid cell along a drainage network. This method accounts for the spatially variable properties within contributing drainage basin areas as debris flows travel through the drainage network. Applying the models along drainage networks, rather than to an entire drainage basin, provides hazard assessments that identify the potential impacts within the primary channels of a watershed, where destructive debris flows may both erode and deposit large volumes of material.